To the right of the verb : an investigation of clitic doubling and right dislocation in three Spanish dialects - Belloro, Valeria A. (Cambridge Scholars Publishing, 2015)
This book provides a new approach to the study of clitic doubling in Spanish, based on spontaneous data considered within their broad discourse context, and focusing on the cognitive and pragmatic factors that underpin the use of these constructions. Considering examples from Argentine, Mexican and Spanish regional variants of the language, the study embraces the graduality and heterogeneity that emerge from the data, and distinguishes different subtypes of "doubling" depending on the pragmatic constraints that govern their use, as well as the morphophonological and morphosyntactic characteris.